Вплив кліностатування на структурні показники люцерни посівної за умови взаємодії з Sinorhizobium meliloti - Viter, A.V.; Ivanytska, B.O.; Mamenko, P.M.; Miskiv, N.H. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
Investigation of clinorotation, spontaneous infection of alfalfa cv. Yaroslavna with Sinorhizobium meliloti and its induced inoculation with S. meliloti str. 441 are shown simulated microgravity to depress root growth, stimulate leaf area increasing and decrease leaf mass per unit of area. Proper nitrogen nutrition (resulted by interaction of alfalfa with effective rhizobial strain) facilitates shoot growth and organogenesis as well as manifestation of effects caused by clinorotation.